A Security-Enhanced One-Time Payment Scheme for Credit-Card - LI, Yingjiu (Institutional Knowledge at Singapore Management University, 2001)
Traditional credit card payment is not secure as semi-secret credit card numbers are repetitively used. One-time transaction numbers have been recently proposed to enhance the security in credit card payment. Following this idea, we use a hash function in generation of one-time credit card numbers: the next one-time number is computed by hashing the current one-time number with a secret that is known only by card holder and issuer. Compared with related work, our scheme places less burden on credit card issuers, and can be easily deployed in both on-line and offline payment scenarios.